PENERAPAN SISTEM KAS KECIL PADA SEKOLAH DASAR ISLAM TERPADU DI KAWASAN KABUPATEN SERANG - Muhammad Angga Anggriawan (LP2M Universitas Bina Bangsa, 2022)
The petty cash system is an information system that is included in financial accounting standards that must be applied to the financial management of an entity, including business institutions. The application of a petty cash system will certainly make it easier when conducting transactions that are frequent and have a small nominal value because the use of checks or bank checking accounts is certainly considered ineffective. This study aims to determine how the application of the petty cash system in an integrated Islamic elementary school in the Serang Regency area. The method used in this study is a descriptive analysis method that collects data for interpretation, so as to provide an overview of the objects and problems studied. The type of research used in this study is a qualitative approach. The research population is SDIT which is located in Serang Regency. The results of the study show that financial management at the Integrated Islamic Elementary School in the Serang Regency area is currently still not well managed. This is due to the fact that the petty cash system has not yet been implemented in financial management